Psychological stress and its relationship with metacognitive thinking during blended learning among a sample of graduate students in educational studies at King Abdulaziz University in Jeddah - Al-Rehaili, Maryam Saad Bashir; Al-Amir, Eman Mohammed Yahya; Baamer, Manal Yahya (Journal of Educational and Psychological Sciences, 2025)
The aim of the study is to determine the level of psychological stress and metacognitive thinking and the relationship between them during blended learning, in addition to recognizing the impact of the following variables on each of psychological stress and metacognitive thinking: (educational level, specialization, social status, residence, economic status) in a sample of female students in the Faculty of Graduate Studies at King Abdulaziz University. The study sample consisted of (123) female students, which adopted the descriptive correlative approach. The results of the study concluded that there is a statistically significant inverse correlation between psychological stress and metacognitive thinking during blended education. In addition, the results indicated that the level of psychological stress during blended education was average in the study sample, while the level of metacognitive thinking was high among the sample. The results also show that there are no statistically significant differences in the level of psychological stress due to the variable of educational level, specialization, residence during the blended education. In the same regards, there are statistically significant differences due to the variable social status and economic status during the blended education. Finally, there are no statistically significant differences in the level of metacognitive thinking due to the variable of educational level, specialization, marital status, residence, economic status during blended education. In light of these results, the following recommendations are considered: - Develop mentoring programs on a range of strategies and methods to cope with psychological stress. -Preparing virtual classes aimed at explaining how curriculum requirements and costs are fulfilled. -Hold courses or seminars to illustrate the skills of metacognitive thinking and how to use them.